Description of Picture with Application of Knowledge about Perspective during Teacher Training Practice at School - I. Grakhova, Svetlana (2019)
The article covers one of the aspects of teaching students a methodology of perspective analysis of paintings at classes of fine arts, as well as a possibility of applying the knowledge about perspective at lessons on writing and speech activity development dedicated to writing essays-descriptions of artistic canvases. The authors of the article introduce a sequence for analyzing perspective images. They suggest viewing pictures on the basis of determination of their main elements: right choice of viewpoint and of horizon line height, location of the interior, lighting and reflection conditions of the objects. All this allows revealing the plot of a work of art and defining its compositional center as an important component enhancing the emotional impact on a viewer. Particular attention has been paid to a verbal description - interpretation of artistic works. Meeting modern requirements on the arrangement of studies at secondary schools, this article offers a plan of a writing and speech activity development lesson devoted to writing essays-descriptions of pictures.